2014
DOI: 10.1002/fam.2287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high temperature on the residual mechanical performance of concrete made with recycled ceramic coarse aggregates

Abstract: SUMMARYThis paper presents an experimental study on the residual mechanical properties of concrete with recycled ceramic coarse aggregate (RCCA) after exposure to elevated temperatures. Four concrete mixes were produced: a control concrete and three concrete mixes with replacement ratios of 20, 50 and 100% of natural aggregate (NA) by RCCA. The specimens were subjected to temperatures of 200, 400 and 600°C, for a period of 60 min. After cooling down to room temperature, the following concrete properties were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
4
20
0
1
Order By: Relevance
“…The reasons for better performance of ceramic sand concrete can be (1) ceramic sand has lower mass loss at elevated temperature than natural sand as observed in TGA (Figure ), (2) ceramic concrete has better mechanical properties at laboratory temperature, and (3) less volume changes in ceramic sand concrete results in lower stresses and hence no cracks appear on surface. Similar observations were made by Halicka et al and Martins et al in their studies.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The reasons for better performance of ceramic sand concrete can be (1) ceramic sand has lower mass loss at elevated temperature than natural sand as observed in TGA (Figure ), (2) ceramic concrete has better mechanical properties at laboratory temperature, and (3) less volume changes in ceramic sand concrete results in lower stresses and hence no cracks appear on surface. Similar observations were made by Halicka et al and Martins et al in their studies.…”
Section: Resultssupporting
confidence: 92%
“…Overall, they observed that water cooling caused higher loss in compressive strength due to thermal shock. Matrins et al investigated the residual mechanical properties of recycled ceramic aggregate (construction and demolition waste) concrete subjected to elevated temperature. They reported that concrete samples with brick aggregate resulted in explosive spalling whereas concrete samples with recycled concrete aggregate displayed improved residual mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the behavior of recycled aggregate concrete at elevated temperatures is researched in limited number of studies. And most of them evaluated the residual mechanical properties of recycled aggregate concretes after exposure to elevated temperatures . Sarhat and Sherwood studied the residual compressive strength, split tensile strength, and modulus of elasticity of concrete containing various amounts of recycled coarse aggregate (RCA) after exposure to elevated temperatures up to 750 °C.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the need for seeking new applications in other industries where the ceramic waste can be recycled is becoming absolutely vital (3). Although the reutilization of ceramic waste as fine and coarse aggregates in the concrete production has been previously studied (4)(5)(6)(7), its use in structural concrete is not a common practice, particularly as fine aggregates (8). Thus, it seems that the best engineering applications found for recycling ceramic waste is as in non-structural concretes as recycled aggregates.…”
Section: Introductionmentioning
confidence: 99%